The factors that affect the learning of students in the 3rd year of the Faculty of Natural Sciences Savannakhet University - PHONESAY, Latsamy (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this research was to analyze the factors that affect the students’ learning of sophomore at the Faculty of Natural Science. The sampling was 91 of sophomore at Faculty of Natural Science, the data was analyzed by using SPSS for WINDOWS to generate descriptive statistics and the analysis was analyzed by (Enter Regression Analysis). The results of this research found: factors that affect students learning rather than any factors was the teacher factor, which has an averaged 3.76 and the standard deviation was 0.85. The second was the family factor, which has an average value of 3.74 and the standard deviation was 0.95 and learner behavior, which has an average value of 3.61 and the standard was 0.92. The lowest mean was the learning facilities, which averaged 3.23 and the standard deviation was 1.01 and there are three factors that can predict student achievements are instructors and family factor can predict students’ learning outcomes with a statistical significance of 0.05 but the learner’s behavioral factors were related the learning outcomes with a statistical significance of 0.01, which can be written as follows: